Smart Systems: Theory and Advances 2022
DOI: 10.51859/amplla.sst631.1122-3
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Results of White Light Generation and Tunable Visible Light Emission by Ag Nanoclusters: Undoped and Doped Tm3+ /Yb3+ Doped Geo2-Pbo Glasses

Abstract: Theory and Advances is licensed under CC BY 4.0.This license requires that reuses give credit to the creator. It allows reusers to distribute, remix, adapt, and build upon the material in any medium or format, even for commercial purposes.The content of the work and its data in its form, correctness and reliability are the sole responsibility of the authors, and do not represent the official position of Amplla Publishing. Downloading and sharing of the work is permitted as long as credit is given to the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 219 publications
(6 reference statements)
2
0
0
2
Order By: Relevance
“…A broad PL band and tunable visible light emission can be observed for the GP 4.5% Ag sample reported in a previous work [39], which is attributed to NCs of varying sizes. As the Ag NC emission peak wavelength is size-dependent, the PL in the blue region corresponds to the emission by smaller-sized Ag NCs.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…A broad PL band and tunable visible light emission can be observed for the GP 4.5% Ag sample reported in a previous work [39], which is attributed to NCs of varying sizes. As the Ag NC emission peak wavelength is size-dependent, the PL in the blue region corresponds to the emission by smaller-sized Ag NCs.…”
Section: Resultssupporting
confidence: 65%
“…GP Tm 2.25% Ag 220 ± 4 GP Tm 4.5% Ag TEM analyses were carried out on the GP 4.5% Ag and GP Tm 4.5% Ag samples, as illustrated in Figure 10. We highlight that the TEM results for the GP 4.5% Ag sample, used as a reference in the present study, were already reported [39], and further analysis is provided in this work.…”
Section: Sample Time (µS)supporting
confidence: 66%
“…Podemos notar que, ao contrário do caso anterior, é preciso um tempo maior para haver a diminuição da concentração de NCs de prata e consequente redução da emissão, para tratamento de 24h; para as amostras tratadas a 470°C com somente 6 horas de tratamento já ocorre diminuição da emissão. A interferência dos íons de Yb 3+ no tamanho dos NCs de prata foi observada em trabalho recente do grupo como mostra claramente a figura 2.25, onde notamos o deslocamento da banda de emissão dos NCs de prata na presença de íons de Yb 3+ [59]. Este fato é também observado na literatura quando são introduzidos íons de Yb 3+ , em matrizes de vidros oxifluoreto [55],…”
Section: Resultados De Nanoclusters De Prata Em Vidros Germanatounclassified
“…É observado também que o aumento do tempo de tratamento para o material favorece a formação das NPs de prata; neste processo a viscosidade e temperatura do tratamento térmico no material são importantes [38]. Temperaturas de tratamento térmico acima da temperatura de transição vítrea reduzem a viscosidade do material, aumentando a taxa de formação dos aglomerados de prata, originando em consequência as NPs de prata; temperaturas inferiores à de transição vítrea favorecem a formação de NCs de prata e dificultam a formação de NPs de prata [35,39]. As transições dos estados de energia permitidas por spin ocorrem entre estados singletosingleto e entre estados tripleto-tripleto, apresentando tempo de vida relativamente rápidos.…”
Section: Nanoclusters Metálicos De Prata: Formação E Definiçãounclassified